Advanced Gear Engineering (Mechanisms and Machine Science,, 2018)
This book covers recent developments in practically all spheres of mechanical engineering related to different kinds of gears and transmissions. Topics treated range from fundamental research to the advanced applications of gears in various practical fields, prospects of manufacturing development, results and trends of numerical and experimental research of gears, new approaches to gear design and aspects of their optimization synthesis. .